2023
DOI: 10.3390/ma16072541
|View full text |Cite
|
Sign up to set email alerts
|

A New Environmentally Friendly Mortar from Cement, Waste Marble and Nano Iron Slag as Radiation Shielding

Abstract: Improving mortar shielding properties to preserve environmental and human safety in radiation facilities is essential. Conventional cement mortars, composed of cement, water, and lime aggregate, are crucial for radiation shielding. Using recycled aggregates to produce new mortar and concrete compositions has attracted the attention of several researchers. In the current study, waste marble and iron slag as aggregates are used to create novel cement mortar compositions to study the aggregate’s impact on the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Moreover, the outcomes showed that above 356 keV, both experimental and calculated values agreed. In another work, El-Khatib et al 10 manufactured a mortar made from cement, marble, and nano- and microsized iron slag (wastes from the marble and steel industry) to investigate the shielding characteristics depending on the iron particle size. The samples, with dimensions of 30 mm in diameter and 5 mm in height, were experimentally examined using 241 Am, 133 Ba, 137 Cs, 60 Co, and 152 Eu point sources, and the obtained values were compared to the calculated values from the XCOM program.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the outcomes showed that above 356 keV, both experimental and calculated values agreed. In another work, El-Khatib et al 10 manufactured a mortar made from cement, marble, and nano- and microsized iron slag (wastes from the marble and steel industry) to investigate the shielding characteristics depending on the iron particle size. The samples, with dimensions of 30 mm in diameter and 5 mm in height, were experimentally examined using 241 Am, 133 Ba, 137 Cs, 60 Co, and 152 Eu point sources, and the obtained values were compared to the calculated values from the XCOM program.…”
Section: Introductionmentioning
confidence: 99%